Pengaruh Informasi Investasi Dan Overconfidence Terhadap Eskalasi Komitmen - Annisa Rysdi Edfa; Sany Dwita (Universitas Negeri Padang, 2019)
This study aims to examine the effect of investment information and overconfidence in the commitment escalation. The population in this study were students of the Master Program in the Faculty of Economics, Padang State University. A total of 64 people agreed in this study. The hypothesis of this study is managers who experience negative investment information will tend to escalate commitments than managers who receive positive investment information managers with overconfidence will tend to escalate commitments than managers with underconfidence. Laboratory experiments with a 2 x 2 factorial design were carried out. 64 MM and MPdE students—as proxies of project managers—participate in an experiment. One-way ANOVA is used at Hypothesis test. Results that showed significant investment information on the escalation of commitments with a significance value of the One Way ANOVA analysis test of 0.00 <0.05. Overconfidence does not affect managers' decisions in escalating commitments in this study. The significance value of the One Way ANOVA analysis test was 0.74> 0.05.